2015
DOI: 10.4025/actascianimsci.v37i1.24787
|View full text |Cite
|
Sign up to set email alerts
|

<b>Ingestive behavior of crossbred heifers in four seasons related to the structure of stargrass pasture

Abstract: ABSTRACT. The ingestive behavior of crossbred heifers grazing on stargrass pasture was managed at two levels of light interception and two levels of post-grazing residual height. The experiment was conducted at Pesagro (Seropédica, Rio de Janeiro State) between April 2012 and January 2013. The grazing (GT), rumination (RT) and idling (IT) times were evaluated every 10 minutes throughout a 24-hour period. Forage samples were collected for the analysis of chemical composition and for leaf:stem ratio determinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Castro et al (2009), working with heifers, found similar behaviour and explained it by the greater temperature and sunshine at these times. The ingestive behaviour of ruminants has a heterogeneous nychthemeral distribution and is aff ected by such factors as management, nutrition and environmental conditions, especially temperature (CAMPANA et al, 2015), which would explain the results for idle time.…”
Section: Variablementioning
confidence: 99%
“…Castro et al (2009), working with heifers, found similar behaviour and explained it by the greater temperature and sunshine at these times. The ingestive behaviour of ruminants has a heterogeneous nychthemeral distribution and is aff ected by such factors as management, nutrition and environmental conditions, especially temperature (CAMPANA et al, 2015), which would explain the results for idle time.…”
Section: Variablementioning
confidence: 99%
“…Considering the different chemical and physical composition from conventional foods, the use of alternative food should be accompanied by assessments of the feeding behavior of the animals, as these serve as a tool for evaluating diets, allowing feeding management to achieve better performance, as cattle respond differently to various types of food, changing the feeding habits and production levels (Antunes et al, 2014;Pina et al, 2006;Riaz, Südekum, Clauss, & Jayanegara, 2014;Campana et al, 2015;Pimentel et al, 2015;Silva et al, 2005a;b).…”
Section: Introductionmentioning
confidence: 99%